2022
DOI: 10.1186/s12902-021-00923-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis of papillary thyroid carcinoma in the context of Hashimoto’s thyroiditis

Abstract: Background Whether Hashimoto’s thyroiditis (HT) affects the lymph node metastasis of papillary thyroid carcinoma (PTC) remains uncertain. The diagnostic criteria for HT differed in previous studies. Our study focused on analysing the influence of HT on PTC lymph node metastasis (LNM) with stringent diagnostic criteria for HT. Methods A total of 444 patients diagnosed with PTC from 2019 to 2020 were enrolled and divided into two groups: HT group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
5
1
Order By: Relevance
“…The present study discovered that ETE is a risk factor for CLNM and LLNM in MPTC. However, Hashimoto’s thyroiditis was not classified as a risk factor for CLNM and LLNM, which was inconsistent with published results ( 37 , 38 ). This discrepancy might be caused by differences in the selection criteria and study designs.…”
Section: Discussioncontrasting
confidence: 86%
“…The present study discovered that ETE is a risk factor for CLNM and LLNM in MPTC. However, Hashimoto’s thyroiditis was not classified as a risk factor for CLNM and LLNM, which was inconsistent with published results ( 37 , 38 ). This discrepancy might be caused by differences in the selection criteria and study designs.…”
Section: Discussioncontrasting
confidence: 86%
“…Many authors have reported a considerably better prognosis of DTC when HT is also present; however, these data are not uniform in the various studies, as some report a greater presence of multifocal carcinomas and a similar recurrence rate to non-HT tumors (20, 21), while others show a greater presence of microcarcinomas, with a smaller average tumor size and a lower incidence of lymph node metastases and extrathyroidal extension, leading to significantly better disease-free survival for DTCs with concomitant HT than for those without HT (16,22,23,38).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified HT as an independent risk factor for thyroid cancer. The proportion of multifocality in PTC patients with HT is higher than in those without, while the incidence of lymph node metastasis is comparable ( 30 , 31 ). Salvatore Ulisse et al.…”
Section: Discussionmentioning
confidence: 96%